Desenvolvimento do aplicativo móvel rastreio do câncer de boca (RCB) para a realização de triagem do câncer bucal - Gomes, Mayra Sousa (2015)
Introduction: Mobile applicative (apps) development is a relatively new phenomenon that is increasing rapidly due to the popularity and portability of smartphones. The idea to use apps to screening oral conditions is still a novelty. Purpose: The aim of this study was to develop a mobile applicative focusing oral cancer screening. Methods: The app content comprised questions about oral cancer profile and short videos of oral examination. The development of this app was performed by a team formed by technology of information professionals and oral pathologists. The app development process was made following the steps: 1) reality and risk factors study, observing the real conditions of collection of data 2) development phase, with implementation of the needs observed in the field study and 3) field test, when the implementation passed by some refinement or even redraw. The app was developed using Android system (4.4.2 version), with JAVA language and focused sociodemographic data, risk factors for oral cancer, tobacco and alcohol uses, solar exposition and other contributing factors such unprotect oral sex, oral pain and prosthesis use. Afterwards, we obtained data of survey of a high risk population for oral cancer and evaluated the sensitivity/specificity/ accuracy and predictive values of clinical oral diagnosis between two blinded trained examiners, who used movies and data from the app, and in loco oral examination as gold standard. This trainning process with examiners was divided in theorical and practical approaches during 8 hours. Results: On reality and risk factors study, we percept the need of clarification of some questions about use of prosthesis as well to establish better conditions to make movies on external light. We modified the initial version and performed the followed to field test with good comprehension and adequacy. On survey/ concordance analysis, we evaluated 55 high risk individuals for oral cancer. Of them, 31% presented homogeneous/heterogeneous white lesions with possible potential of malignancy. Regarding clinical diagnosis by examiners using videos, when compared with the gold standard, the sensitivity was between 82% and 100% (average 91%), specificity between 81% and 100% (average 90.5%) and accuracy from 87.27% to 95.54% (average 90.90%), and considering found lesions. Evaluating the examiner with better concordance with gold standard for risk lesions, the kappa value between than was 0.597. Conclusion: Mobile app with videos and data collection could be an interesting alternative to oral examination and physical formularies filling on oral cancer surveys.